Localization patterns of gold mineralization in the Phuoc Son area, Central Vietnam - T. Tran Van; P. A. Ignatov; T. Mai Trong (Известия высших учебных заведений: Геология и разведка)
Background. In this paper, the authors aim to reveal the localization patterns of gold mineralization in the Phuok Son region of Central Vietnam, which formed a Proterozoic-Cambrian metamorphic complex in the zone of the Late Paleozoic Benzhang–Queshon granite block.Aim. To determine the localization patterns of gold mineralization in the Phuoc Son area, Central Vietnam.Materials and methods. The research was based on geological materials, as well as mine working and appraisal well data. The material composition of the materials was studied using 15 transparent sections and 18 polished sections. In total, 127 samples were subjected to atomic absorption spectroscopy.Results. Within the Phuoс Son gold ore field in Central Vietnam, the site of the Baidat and Baigo mines located in the zone of reverse-shear termination was investigated. Here, the gold ore bodies are represented by quartz-sulfide veins subparallel to schistosity. The ore-bearing zones are layered zones of tectonic faults, which formed at the end of the reverse-shear period and complicated the western limbs and locks of the anticlines. These zones were formed under regional sublatitudinal horizontal stresses. The horizons of carbonaceous quartz-sericite schists are of great importance in ore control. There are steeply dipping post-ore faults that displace ore bodies. Two gold mineralization stages can be distinguished. The early stage was characterized by a wide development of sphalerite and a smaller amount of gold. The later stage was associated with the main precipitation of gold and formation of galena. According to the geochronological data on the argon isotopy in biotite, the gold mineralization at Baidat and Baigo was probably formed in the Triassic (250–200 Ma ago), at the stage of extinction of the regional metamorphism of the Indosinian orogenyConclusion. The results obtained should be used when conducting local forecasting of gold deposits in Central Vietnam.